Depositing Corporate Payout - Lin, Leming (Journal of Financial and Quantitative Analysis, 2026)
This article studies the flow of payout funds in the financial system. Using various data sources and empirical strategies, it provides evidence that a significant portion of payouts enters the banking sector as deposits, which are then intermediated to bank borrowers. The findings highlight an important channel through which corporate payout policies shape capital allocation in the economy and suggest that policies aimed at restricting payouts may distort this process by limiting the flow of funds from large and profitable corporations to small, bank-dependent firms and households.